Processes Complicating the Activity of the Modern Leader - Yuldashev B. E. (International Journal on Integrated Education, 2022)
This article talks about the processes that complicate the activity of a modern leader, including the economic reforms implemented in Uzbekistan during the years of independence, the restoration of national values, the strengthening of political demands placed on leaders, the development of civil society institutions in the country, the sharp increase in freedom of speech and transparency in Uzbekistan, the coronavirus pandemic, etc. It has been scientifically analyzed that it served as a factor complicating the leader's activity.